Revision Surgery after Percutaneous Endoscopic Transforaminal Discectomy Compared with Primary Open Surgery for Symptomatic Lumbar Degenerative Disease - Jin‐qian Liang; Chong Chen; Hong Zhao (Orthopaedic Surgery, 2019)
Objective To evaluate the clinical outcome of reoperation after percutaneous endoscopic lumbar discectomy (PELD) as compared with primary spinal decompression and fusion. Methods A retrospective study from December 2014 to December 2017 was conducted at Peking Union Medical College Hospital and comprised 39 patients with symptomatic lumbar degenerative disease (LDD): 13 post‐PELD who underwent reoperation (revision surgery group) and 26 who received primary spinal decompression and fusion (primary open surgery group). The two groups were compared regarding: operative time, blood loss, transfusion, hospitalization, postoperative visual analog scale (VAS) scores, Oswestry Disability Index (ODI) scores, Japanese Orthopedic Association (JOA) improvement rate, and postoperative complications. The Mann–Whitney U‐test was applied to analyze continuous parameters, and the χ2‐test for categorical parameters. Fisher's exact test was used for small data subsets. Results There was no statistically significant difference between the two groups in mean age (52.7 years vs 52.9 years), gender ratio (6 men‐to‐7 women vs 12 men‐to‐14 women), body mass index, medical history, preoperative diagnosis, or surgical spine level (P > 0.05). The mean operative time of the revision surgery group was significantly longer than that of the primary open surgery group (160.0 min vs 130.2 min, P < 0.05). The revision surgery group also had a significantly higher mean estimated blood loss, postoperative drainage, and length of hospital stay (P < 0.05). However, no significant differences were found between the two groups in terms of hemoglobin and hematocrit values, preoperatively and postoperatively. The rate of transitional neurological irritation was higher in the revision surgery group (61.5% vs 3.8%; P < 0.05), as was intraoperative durotomy and cerebrospinal fluid leakage (30.8% vs 3.8%, P < 0.05). At 1 month, the VAS and ODI scores of the primary open surgery group were significantly better than those of the revision surgery group, while the improvement in JOA scores was similar. After 6 and 12 months’ follow‐up, the VAS and ODI scores and the rates of JOA improvement were comparable. Conclusion Patients with LDD who received primary spinal decompression and fusion experienced lower rates of perioperative complications and shorter hospitalization compared with patients who underwent revision surgery after PELD, but the clinical outcomes at the last follow‐up of both groups were satisfactory.